The Influence of Financial Technology Payment, Financial Knowledge, and Income on Financial Management Behavior (Case Study: College Students in Subang) - Inten Handa Moorjati; Dede Hertina (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the influence of financial technology payment, financial knowledge, and income on the financial management behavior of college students in Subang. The research employs a quantitative method with a descriptive and verificative approach. Data were collected through questionnaires distributed to 100 active college students studying in Subang who utilize financial technology payment in their financial activities. A purposive sampling technique was used to select respondents from various higher education institutions in Subang. Data analysis was conducted using SPSS software to test the validity and reliability of the research instruments and to analyze the relationships between variables. The results indicate that financial technology payment, financial knowledge, and income have a positive and significant impact on college students’ financial management behavior in Subang. However, this study has certain limitations, particularly in the scope of criteria for the financial knowledge variable. Future researchers are encouraged to expand the study beyond college students, incorporate gender diversity, and broaden the scope of variables, especially in terms of financial knowledge aspects.